Cystic Renal Disease in Children: A Broad Spectrum from Simple Cyst to End Stage Renal Failure - ALPAY, HARİKA; GÖKCE, İBRAHİM; YILDIZ, NURDAN (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2019)
Objective: Renal cystic diseases consist of a broad spectrum of hereditary or acquired conditions that may lead to end stage renal disease. We aimed to evaluate our patients diagnosed as renal cystic disease in terms of their diagnosis, demographic findings and clinical follow-up. Materials and Methods: The patients followed between 1993-2015 in our pediatric nephrology outpatient department with renal cystic diseases were evaluated retrospectively. Results: In 237 patients, 110 (46.41%) were female, 127 (53.59%) were male. One hundred-eight (45.56%) patients were diagnosed antenatally, the mean age at diagnosis was 7.23 +/- 4.72 (0-17) years in 129 patients. The diagnosis were simple-cyst in 36 (15.18%), multicystic displastic kidney disease in 112 (47.25%), autosomal dominant polycystic kidney disease in 56 (23.62%), autosomal recessive polycystic kidney disease in 22 (9.28%), cyst hydatic in three (1.26%), Joubert sydrome in two, nephronophthisis in one, tuberosclerosis in two, Bardet-Biedl syndrome in three patients. Five patients (2.1%) died and ten (4.21%) patients progressed to chronic kidney injury. Proteinuria was found in 15 (6.32 %) and hypertension in 10 (4.21%) patients. Conclusion: Renal cystic disease is an important group that can lead to proteinuria, hypertension and end stage kidney failure. Periodic follow-up is important in these patients to avoid and treat the complications early and properly.
Keywords: Renal cyst; kidney failure; proteinuria; hypertension; KIDNEY